2017
DOI: 10.3171/2017.6.focus17256
|View full text |Cite
|
Sign up to set email alerts
|

The hypothalamus at the crossroads of psychopathology and neurosurgery

Abstract: The neurosurgical endeavor to treat psychiatric patients may have been part of human history since its beginning. The modern era of psychosurgery can be traced to the heroic attempts of Gottlieb Burckhardt and Egas Moniz to alleviate mental symptoms through the ablation of restricted areas of the frontal lobes in patients with disabling psychiatric illnesses. Thanks to the adaptation of the stereotactic frame to human patients, the ablation of large volumes of brain tissue has been practically abandone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 102 publications
0
31
0
3
Order By: Relevance
“…Through a vast array of neural connections, it receives input from both spinal cord and brainstem nuclei as well as corticolimbic structures. This information is integrated within dedicated hypothalamic nuclei, altered through secondary and tertiary hypothalamic relay stations and then conveyed to autonomic and limbic control centers where the appropriate physiological response is orchestrated across organ systems 3 . Apart from axonal projections, the hypothalamus further shapes the physiological response via engagement of the pituitary gland and release of hormones into the bloodstream 4 .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Through a vast array of neural connections, it receives input from both spinal cord and brainstem nuclei as well as corticolimbic structures. This information is integrated within dedicated hypothalamic nuclei, altered through secondary and tertiary hypothalamic relay stations and then conveyed to autonomic and limbic control centers where the appropriate physiological response is orchestrated across organ systems 3 . Apart from axonal projections, the hypothalamus further shapes the physiological response via engagement of the pituitary gland and release of hormones into the bloodstream 4 .…”
Section: Background and Summarymentioning
confidence: 99%
“…In addition, hemispheric and gender-specific volumes were normalized by hemispheric and total brain volume, respectively, to account for interindividual variability (Supplementary Tables 4 and 5). www.nature.com/scientificdata www.nature.com/scientificdata/ The mean absolute volume (± SD) of the segmented hypothalamus was 832.9 mm 3 (± 107.59 mm 3 ; left: 429.54 mm 3 ± 55.23 mm 3 ; right: 403.39 mm 3 ± 53.09 mm 3 ). Owing to an overall increase in brain volume, the mean volume in the male subgroup (892.5 mm 3 ± 99.5 mm 3 ; left: 459.82 mm 3 ± 51.55 mm 3 ; right: 432.64 mm 3 ± 48.90 mm 3 ) exceeded the values measured in the female subgroup (782.1 mm 3 ± 86.05 mm 3 ; left: 403.67 mm 3 ± 44.00 mm 3 ; right: 378.41 mm 3 ± 42.78 mm 3 ) (Fig.…”
Section: Volumetric Analysis Volumetric Analyses Of Parcellated Hypomentioning
confidence: 99%
“…I the only case of hypothalamotomy analyzed, the authors reported that the patient had a rapid improvement in aggressiveness and resumed social interactions, 13 but this was to be expected, as the hypothalamus is considered to be associated with aggressive behavior. 14 It is important to note that, despite the improvement in the negative symptoms revealed in an anterior capsulotomy, there were improvements in the positive symptoms in all studies. Thus, the exploration of new targets based on the neurocircuitry involving schizophrenia, as well as the use of multiple targets, should be addressed, seeking to cover the full spectrum of symptoms, such as those involving the NAcc, the GP, and the VTA.…”
Section: Discussionmentioning
confidence: 79%
“…Better results with fewer side effects were possible thanks to the advances in imaging techniques and the rise of the stereotactic surgery. The surgery has enabled the location of the targets with high precision and minimal tissue damage, 4,14,48 which is noticeable when establishing a temporal line in the results presented, dividing the conventional leucotomies, as in the study by Benson et al, 15 of the procedures using a stereotactic technique.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, hypothalamic stimulation can also induce pleasurable experiences and prosocial behavior in humans [53,54]. For instance, several investigations demonstrated reduced aggressive behavior and increased social interactions after deep brain stimulation of the posteromedial hypothalamus [55].…”
Section: Introductionmentioning
confidence: 99%